ANALISIS EFEKTIVITAS PENGELOLAAN ZAKAT PRODUKTIF DALAM MENINGKATKAN KESEJAHTERAAN EKONOMI UMAT (Studi Kasus di Lazismu Purbalingga) - Riri Dwi Nursalimah; Jamal Abdul Aziz (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to analyze the management of productive zakat implemented by LAZISMU Purbalingga as an effective and sustainable model for empowering mustahik in improving their economic conditions. LAZISMU Purbalingga has carried out various programs such as business capital provision, skills training, and business mentoring, integrating religious values with professionalism. The research employs a qualitative approach with a single-case study design. Data were collected through in-depth interviews with zakat managers and mustahik, field observations, and document analysis. Data validity was ensured through source triangulation, member checks, and peer debriefing, while data analysis was conducted using reduction, thematic categorization, and in-depth interpretation. The findings reveal that the productive zakat programs have successfully increased mustahik’s income, reduced their dependence on consumptive zakat, and encouraged business independence. The main supporting factors include continuous mentoring, relevant training, and sufficient access to capital. However, limited zakat funds and inadequate managerial skills among mustahik remain significant challenges. This research contributes to the development of productive zakat literature and offers strategic recommendations for zakat institutions to strengthen sustainable economic empowerment programs for the Muslim community.